Firm productivity growth and the knowledge of new workers - Michael Kirker; Lynda Sanderson (New Zealand Government, The Treasury, 2022)
Linked employer-employee data from New Zealand is used to study the relationship between a firm's productivity growth and its exposure to outside knowledge through the hiring of new workers with previous work experience. The estimated relationship between productivity growth and hiring is compared to the predictions implied by two different channels: worker quality and knowledge spillover. Although it is not possible to identify a causal relationship, the productivity of a worker's previous employer is correlated with subsequent productivity growth at the hiring firm. The patterns of this correlation are consistent with both the worker quality and knowledge spillover channels operating simultaneously. Furthermore, if knowledge spillover is occurring, the results suggest the type of knowledge spilling over relates to technological knowledge allowing firms to become more capital intensive, rather than knowledge that improves the efficiency of utilising existing inputs.
Keywords: D24; J24; J62; O33; 330; productivity; labour mobility; human capital; knowledge diffusion